(untitled) (KYAMC Journal, 2021)
Background: Healthy lifestyle is one which helps keeping and improving health and well-being. This means maintaining hygiene, eating balanced diet, getting regular exercise, avoiding tobacco and drugs and getting adequate rest and recreation. Objective(s): To assess healthy lifestyle practice among selected rural-community of Sirajganj district. Materials and methods: This cross-sectional study was conducted among people living in selected villages of Sirajganj. A total of 490 respondents were interviewed face-to-face using a semi-structured questionnaire. Results: Among the respondents 73.3% were female, mean age was 40.29 ± 15.84 years and 56.9% were literates. Mean monthly income was 10812.30±10039.63 taka. Majority (97.3%) said that they wash their hands ’before eating’, 89.0% said ’after coming from washroom’, 18.6% mentioned of ’after coming in contact with sick person’, 3.9% said ’after playing and 3.1% mentioned of ’after holding coins’. About 84% used soap and water for hand washing. One third (33.9%) washed their hands for a period of more than 20 seconds. About 28% consume meat, fish, and egg daily. Majority (77.8%) consumed extra salt daily, 81.8% never took part in playing of doing exercises and 9.8% were current smokers. Conclusion: Subjects were ruralpeople and showed lack of many elements of healthy lifestyle. Proportion of tobacco-use was less. Yet a big proportion consumes extra salt, don’t do any exercise, don’t eat fruits and cannot eat protein rich food. KYAMC Journal Vol. 11, No.-4, January 2021, Page 193-198